2023
DOI: 10.3390/microorganisms11030628
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Artificial Mouth for Dental Caries Development

Abstract: This study validated a microbial caries model (artificial mouth) for dental caries development to determine the optimal time to create early caries suitable for evaluation of the efficacy of caries therapeutic agents. In all, 40 human enamel blocks were placed in an artificial mouth at 37 °C and 5% CO2 and were exposed to brain heart infusion broth inoculated with S. mutans in continuous circulation (0.3 mL/min). The culture medium was replaced three times daily. Samples were exposed to 10% sucrose for 3 min, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Although most marketed mouthwashes are applied for 30 s, the isomalt mouthwashes investigated in the present study were tailored for 1-min application, thus the 1-minute application used for all the mouthwashes in the present study as directed by the manufacturer. The study was conducted using a multispecies MCM that acts as an artificial mouth, producing cariogenic dental plaque and simulating the biological and physiological activities observed within the oral environment [11][12][13]. In the present study, the application of the mouthwashes in the presence of plaque, frequently fed with sucrose without toothbrushing, subjected the tooth blocks to the natural demineralization and remineralization cycles similar to a high caries risk condition in the oral environment [12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although most marketed mouthwashes are applied for 30 s, the isomalt mouthwashes investigated in the present study were tailored for 1-min application, thus the 1-minute application used for all the mouthwashes in the present study as directed by the manufacturer. The study was conducted using a multispecies MCM that acts as an artificial mouth, producing cariogenic dental plaque and simulating the biological and physiological activities observed within the oral environment [11][12][13]. In the present study, the application of the mouthwashes in the presence of plaque, frequently fed with sucrose without toothbrushing, subjected the tooth blocks to the natural demineralization and remineralization cycles similar to a high caries risk condition in the oral environment [12].…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted using a multispecies MCM that acts as an artificial mouth, producing cariogenic dental plaque and simulating the biological and physiological activities observed within the oral environment [11][12][13]. In the present study, the application of the mouthwashes in the presence of plaque, frequently fed with sucrose without toothbrushing, subjected the tooth blocks to the natural demineralization and remineralization cycles similar to a high caries risk condition in the oral environment [12]. The result of the study showed that with either the SMH (%ΔSMH) or the TMR (Δz) measurement, combining fluoride with Isomalt and CPC (IFC) consistently showed higher effectiveness in preventing demineralization (87%) than when it is only fluoride (37%) or fluoride combined with either Isomalt (33%) or CPC (58%) only (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is noteworthy that the application of family members of MCM nanomaterials in dentistry is an active area of research that holds potential for various applications in dentistry, such as dental Restorative materials [ 37 ], drug delivery in periodontal therapy [ 38 , 39 ], dental implant coating [ 40 ], remineralizing agents [ 41 , 42 ], local anesthetic delivery [ 43 ], and dental cement [ 44 ]. To the best of our knowledge, there is no study about the application of MCM-48 in the pulpotomy of teeth.…”
Section: Introductionmentioning
confidence: 99%